2020
DOI: 10.1002/hep.30966
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐210 Promotes Bile Acid–Induced Cholestatic Liver Injury by Targeting Mixed‐Lineage Leukemia‐4 Methyltransferase in Mice

Abstract: BaCKgRoUND aND aIMS:Bile acids (BAs) are important regulators of metabolism and energy balance, but excess BAs cause cholestatic liver injury. The histone methyltransferase mixed-lineage leukemia-4 (MLL4) is a transcriptional coactivator of the BA-sensing nuclear receptor farnesoid X receptor (FXR) and epigenetically up-regulates FXR targets important for the regulation of BA levels, small heterodimer partner (SHP), and bile salt export pump (BSEP). MLL4 expression is aberrantly down-regulated and BA homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Hepatic mRNA levels of FXR , as shown previously ( 5 ), and BRD4 were significantly reduced in PBC patients compared with healthy individuals, whereas those of inflammatory genes, IL6 and IL6RA , and fibrotic genes, ACTA2 and COL1A1 , were all substantially elevated in the patients ( Figure 8, A and B ). In previous studies, hepatic mRNA and protein levels of SHP, a target of FXR/BRD4, were not changed in patients with PBC compared with healthy subjects, but nuclear levels of SHP were substantially reduced in the patients ( 42 ). These results suggest that the FXR-BRD4 function is likely dysregulated in patients with PBC.…”
Section: Resultsmentioning
confidence: 82%
“…Hepatic mRNA levels of FXR , as shown previously ( 5 ), and BRD4 were significantly reduced in PBC patients compared with healthy individuals, whereas those of inflammatory genes, IL6 and IL6RA , and fibrotic genes, ACTA2 and COL1A1 , were all substantially elevated in the patients ( Figure 8, A and B ). In previous studies, hepatic mRNA and protein levels of SHP, a target of FXR/BRD4, were not changed in patients with PBC compared with healthy subjects, but nuclear levels of SHP were substantially reduced in the patients ( 42 ). These results suggest that the FXR-BRD4 function is likely dysregulated in patients with PBC.…”
Section: Resultsmentioning
confidence: 82%
“…e negative feedback of bile acid hepatointestinal circulation is mediated by small molecule heterodimer partner (SHP), which is the downstream target of FXR [34]. It was found that the activation of FXR will induce SHP-inhibited expression of CYP7A1 and ASBT in liver cells [35,36]. Binding between SHP and transcription factor LRH-1 will regulate the expression of CYP7A1 in that LRH-1 inhibition will result in the decreased expression of CYP7A1 [37].…”
Section: Discussionmentioning
confidence: 99%
“…In liver, miR-291b-3p promotes lipogenesis by suppressing AMPKα1 expression and activity (31). Hepatic miR-210 is elevated in cholestatic mice and PBC patients, promoting bile acids-induced liver injury by targeting mixed-lineage leukemia-4 (MLL4) (32). In the present study, it was observed that 8 (miR-10b-5p, miR-24-3p, miR-29a-3p, miR-30b-5p, miR-34a-5p, miR-125b-5p, miR-130a-5p and miR-199a-5p) out of these 17 miRNAs associated with hepatic lipid metabolic disorders were downregulated in the livers of SCH mice, suggesting that these miRNAs may be involved in hepatic lipid metabolic disorders in SCH.…”
Section: Discussionmentioning
confidence: 99%